Blurred boundaries: A flexible approach for segmentation applied to the car market - Laura Grigolon (Quantitative Economics, 2021)
Prominent features of differentiated product markets are segmentation and product proliferation blurring the boundaries between segments. I develop a tractable demand model, the Ordered Nested Logit, which allows for asymmetric substitution between segments. I apply the model to the automobile market where segments are ordered from small to luxury. I find that consumers, when substituting outside their vehicle segment, are more likely to switch to a neighboring segment. Accounting for such asymmetric substitution matters when evaluating the impact of new product introduction or the effect of subsidies on fuel-efficient cars.
Keywords: D11; D12; L62; M3; 330; Discrete choice model; Generalized Extreme Value; Ordered Nested Logit